Sphaleron damping and effects on vector and axial charge transport in high-temperature QCD plasmas - De Bruin, Lillian; Schlichting, Sören (Physical review, 2024)
We modify the anomalous hydrodynamic equations of motion to account for dissipative effects due to quantum chromodynamic (QCD) sphaleron transitions. By investigating the linearized hydrodynamic equations, we show that sphaleron transitions lead to nontrivial effects on vector and axial charge transport phenomena in the presence of a magnetic field. Due to the dissipative effects of sphaleron transitions, a wave number threshold 𝑘CMW emerges characterizing the onset of chiral magnetic waves. Sphaleron damping also significantly impacts the time evolution of both axial and vector charge perturbations in a QCD plasma in the presence of a magnetic field. Based on our analysis of the linearized hydrodynamic equations, we also investigate the dependence of the vector charge separation on the sphaleron transition rate, which may have implications for the experimental search for the chiral magnetic effect in heavy ion collisions.
Gesehen am 25.11.2024